Single Women in Popular Culture - Taylor, A. author. aut Link
VIII, 242 p.
Keywords: Single Women in Popular Culture demonstrates how single women continue to be figures of profound cultural anxiety. Examining a wide range of popular media forms, this is a timely, insightful and politically engaged book, exploring the ways in which postfeminism limits the representation of single women in popular culture.